2005
DOI: 10.1074/jbc.m409425200
|View full text |Cite
|
Sign up to set email alerts
|

On the Competition for Available Zinc

Abstract: Extended x-ray absorption fine structure (EXAFS) spectroscopy was combined with thermodynamic and kinetic approaches to investigate zinc binding to a zinc finger (C 2 H 2 ) and a tetrathiolate (C 4 ) peptide. Both peptides represent structural zinc sites of proteins and rapidly bind a single zinc ion with picomolar dissociation constants. In competition with EDTA the transfer of peptide-bound zinc ions proved to be 6 orders of magnitude faster than predicted for a dissociation-association mechanism thus requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 45 publications
(23 reference statements)
6
83
0
Order By: Relevance
“…Such a mechanism has been suggested for zinc transfer between MBLs and EDTA (14). It has been shown earlier for zinc finger peptides that substoichiometric availability of metal ions might lead to the formation of metal ion bridged complexes (51). Thus, we propose the ability of MBLs to form such complexes if the metal ion binding site concentration exceeds the concentration of available metal ions.…”
Section: Global Effects Of Bound Zinc On Structure and Stability Ofmentioning
confidence: 91%
“…Such a mechanism has been suggested for zinc transfer between MBLs and EDTA (14). It has been shown earlier for zinc finger peptides that substoichiometric availability of metal ions might lead to the formation of metal ion bridged complexes (51). Thus, we propose the ability of MBLs to form such complexes if the metal ion binding site concentration exceeds the concentration of available metal ions.…”
Section: Global Effects Of Bound Zinc On Structure and Stability Ofmentioning
confidence: 91%
“…It has been estimated that the interior of cells contain an over-abundance of zinc-binding units, essentially precluding the existence of ''free" zinc [34,35]. Accordingly, recent studies on zinc finger peptides have suggested that in biological systems, zinc exchange is likely to occur not through a dissociation/association mechanism, but rather via mixed ternary complexes, e.g.…”
Section: Mackcdcknkqckcgdkcecsgdkccekycceeasekkccpagckgdckcanc Hcaeqkmentioning
confidence: 97%
“…Accordingly, recent studies on zinc finger peptides have suggested that in biological systems, zinc exchange is likely to occur not through a dissociation/association mechanism, but rather via mixed ternary complexes, e.g. with kinetically labile structural sites [35]. In the light of the idea that the regulation of zinc fluxes, in particular, reversible zinc binding to zinc fingers, is an important mechanism in cellular development and differentiation, we need to better understand the thermodynamics and kinetics of zinc binding to proteins in general.…”
Section: Mackcdcknkqckcgdkcecsgdkccekycceeasekkccpagckgdckcanc Hcaeqkmentioning
confidence: 99%
“…A major issue regarding the question of how zinc is re-distributed in cells is whether zinc is chaperoned and transferred between proteins by zincmediated protein/protein interactions, i.e. without ever being free, 1 or whether zinc ions are generated intermittently from zinc proteins (Heinz et al 2005). It has been argued that re-distribution of zinc cannot be based on specific chaperone proteins because too many would be required to supply all of the many zinc proteins (Bozym et al 2006).…”
Section: Introductionmentioning
confidence: 98%